2011
DOI: 10.1063/1.3631775
|View full text |Cite
|
Sign up to set email alerts
|

Step driven competitive epitaxial and self-limited growth of graphene on copper surface

Abstract: The existence of surface steps was found to have significant function and influence on the growth of graphene on copper via chemical vapor deposition. The two typical growth modes involved were found to be influenced by the step morphologies on copper surface, which led to our proposed step driven competitive growth mechanism. We also discovered a protective role of graphene in preserving steps on copper surface. Our results showed that wide and high steps promoted epitaxial growth and yielded multilayer graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…After dissolving the underlying copper substrate in FeCl 3 aqueous solution (1 M), the floating CVD-grown graphene film 7 was transferred onto epitaxial p-GaN and n-GaN substrates which were grown on (0001) oriented sapphire substrates by metal organic chemical vapor deposition (MOCVD). The p-GaN sample contains unintentionally doped GaN (u-GaN) layer (2 mm) and p-type GaN:Mg layer (0.2 mm) in sequence.…”
Section: Methodsmentioning
confidence: 99%
“…After dissolving the underlying copper substrate in FeCl 3 aqueous solution (1 M), the floating CVD-grown graphene film 7 was transferred onto epitaxial p-GaN and n-GaN substrates which were grown on (0001) oriented sapphire substrates by metal organic chemical vapor deposition (MOCVD). The p-GaN sample contains unintentionally doped GaN (u-GaN) layer (2 mm) and p-type GaN:Mg layer (0.2 mm) in sequence.…”
Section: Methodsmentioning
confidence: 99%
“…Such findings can be attributed to stepdriven competitive epitaxial and self-limited growth of graphene. 19 It is also observed that near a big domain, a small domain exists as indicated by the arrow, suggesting that when methane is introduced into the reaction tube, many seeds/islands nucleate and grow into domains at certain positions. When graphene domains grow larger, new islands nucleate at the same time, which means not all domains nucleate simultaneously.…”
mentioning
confidence: 98%
“…While no further nucleations were observed for the main graphene layer after the near instantaneous nucleations, secondary layers of graphene emerge around the nucleation centers of the already growing graphene flakes (Figure a). These secondary nucleations were only observed under larger flakes, resulting in smaller flakes enlarging and adhering to the top layer from their underside . The growth of these secondary layers continued until the first monolayer completely covered the surface.…”
mentioning
confidence: 99%